The bioprecipitation of calcium carbonate by native microbial population as a restoration method (Nexo Revista Científica, 2015)
A selection of 30 previously isolated bacteria of different types were taken, mainly Bacillus, which had been previously identified by microbiological and molecular methods to be epilithic biofilms from Chapultepec's Castle in Mexico City, DF. Different methodologies were practiced to determine which of them were forming biofilms and their quantification, the ureasa test and the production of crystals of calcium carbonate in Petry plate with Luria Bertani enriched with calcium carbonate to 0.2 %. The crystals obtained were submitted to diffraction of X-rays and Electronic Microscopy of Sweep. The results show that all microorganisms tested were involved in the process of biofilm formation, and only 12 isolates, including the IS16 (Bacillus subtilis); IIS15a (Bacillus cereus) and IIIS10 (Bacillus subtilis) strains, were the best biofilm formers with high UFC / mL, good in terms of bioprecipitation of carbonates. Particularly, the strains IIIS4 (Bacillus megaterium), IS5 (Bacillus subtilis), IIIS9b (Bacillus subtilis), 21 (Pantoea agglomerans) and IIIS5 (Bacillus simplex). May be some of the microorganisms could be capable of producing urease, to induce precipitation of calcite that contributes to the restoration. As of now, little is known about the participation of Pantoea agglomerans in processes of biorrestauration by means of bioprecipitation of crystals of calcium carbonate and due to the fact that a good response was obtained from the test of ureasa and the crystals obtained were mainly Calcita (99 %), this work shows the feasibility of using this native microorganisms for their activation to achieve the restoration of the worn monuments.